2016
DOI: 10.1158/2326-6066.cir-15-0255
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression and Splicing of ESRP1 in Malignant Melanoma Correlates with Epithelial–Mesenchymal Status and Tumor-Associated Immune Cytolytic Activity

Abstract: Melanoma is one of the major cancer types for which new immune-based cancer treatments have achieved promising results. However, anti-PD-1 and anti-CTLA-4 therapies are effective only in some patients. Hence, predictive molecular markers for the development of clinical strategies targeting immune checkpoints are needed. Using The Cancer Genome Atlas (TCGA) RNAseq data, we found that expression of ESRP1, encoding a master splicing regulator in the epithelial-mesenchymal transition (EMT), was inversely correlate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 35 publications
1
46
0
1
Order By: Relevance
“…This is in agreement to pancreatic ductal adenocarcinoma where increased ESRP1 expression was related to better survival [18], but in contrast to breast cancer patients where ESRP1 was associated with lower survival rate [16]. Recent findings in melanoma patients identified a link between low ESRP1 expression in tumor tissue and tumor-associated immune cytolytic activity with better patient survival [29]. Whether ESRPs play a positive and/or negative role during cancer progression in specific tumors must be elucidated on a tumor-by-tumor basis and considering homogeneity of tumor tissue.…”
Section: Discussionsupporting
confidence: 72%
“…This is in agreement to pancreatic ductal adenocarcinoma where increased ESRP1 expression was related to better survival [18], but in contrast to breast cancer patients where ESRP1 was associated with lower survival rate [16]. Recent findings in melanoma patients identified a link between low ESRP1 expression in tumor tissue and tumor-associated immune cytolytic activity with better patient survival [29]. Whether ESRPs play a positive and/or negative role during cancer progression in specific tumors must be elucidated on a tumor-by-tumor basis and considering homogeneity of tumor tissue.…”
Section: Discussionsupporting
confidence: 72%
“…It has been reported that ESRP1 is critical in regulating cancer subtype specific alternative splicing programs and in mediating EMT specific splicing programs [35,36]. This study characterized the mechanisms and effects of ESRP1 on metastatic behavior in EOC.…”
Section: Discussionmentioning
confidence: 92%
“…Knockdown of ESRP1 activity in breast cancer cells restored the non-EMT-inducing isoform of CD44 and suppressed metastasis [50], evidence that ESRP1 acts as an oncogene. ESRP1 acts as a master regulator of EMT in melanoma [51] and somatotroph adenomas [52]. However, upregulation of ESRP1 is correlated with fewer metastasis and better prognosis in pancreatic ductal adenocarcinoma [53], and acts a tumor suppressor in colorectal cancer [54], reflecting the cell type-specific nature of cancer genes [44].…”
Section: Resultsmentioning
confidence: 99%